2021
DOI: 10.1108/jfra-01-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

Product market competition, board gender diversity and corporate sustainability performance: international evidence

Abstract: Purpose This study aims to investigate whether board gender diversity is associated with corporate sustainability performance and whether industry-level product market competition moderates the effect of board gender diversity on corporate sustainability performance. Design/methodology/approach This study uses international data extracted from global ESG data set from Thomson Reuters (Refinitiv) database. Using data of 23,137 firm-year observations from 37 countries, the authors perform regression analyses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 102 publications
(152 reference statements)
2
25
0
Order By: Relevance
“…Following prior studies (e.g., Alves et al 2015;Kamarudin et al 2021;Smith et al 2006), we measure board gender diversity based on the proportion of women on the board of directors by dividing the number of female board members by the total number of directors (DIVBOD). Second, for the robustness analysis, we follow Campbell and Mínguez-Vera (2008) and Miller and del Carmen Triana (2009) by calculating BLAU, which is based on the Blau (1977) index of heterogeneity.…”
Section: Measurement For Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following prior studies (e.g., Alves et al 2015;Kamarudin et al 2021;Smith et al 2006), we measure board gender diversity based on the proportion of women on the board of directors by dividing the number of female board members by the total number of directors (DIVBOD). Second, for the robustness analysis, we follow Campbell and Mínguez-Vera (2008) and Miller and del Carmen Triana (2009) by calculating BLAU, which is based on the Blau (1977) index of heterogeneity.…”
Section: Measurement For Variablesmentioning
confidence: 99%
“…We have also included a country-level variable, FEMLAB, to control the country variable effect on board gender diversity and the CCH relationship. The model further includes fixed effects to control for unobserved time and industry-wide common factors (Wan Ismail et al 2021).…”
Section: Regression Modelmentioning
confidence: 99%
“…This is due to the fact that in preparation of sustainability reports, firms need to face tensions in balancing the often divergent economic, social, and environmental goals. To a certain extent, firms may be lured towards 'greenwashing', as seen in the case of Volkswagen emission scandals, where incomplete or false information was intentionally provided to legitimately appear sustainability-oriented in order to gain economic benefits (Kamarudin et al, 2021). In addition, a study by Chen et al (2015) showed that some firms tended to apply for repetitive disclosures in order to suppress other disclosures, providing evidence for the manipulative power of management regarding these reports.…”
Section: Studies On Sustainability Reportingmentioning
confidence: 99%
“…Conversely, when PEU is low, predictions about the market may be relatively accurate, thus diminishing the need for external and ex-ante information (Gul & Chia, 1994;Naidenova, 2022), and lower usage of SAP. A robust corporate governance apparatus will institutionalise structures to regularly scan the environment to ensure the organisation anticipates changes and implement measures that ensure organisational survival (Kamarudin et al 2021). Therefore, H6: High level of perceived environmental uncertainty will drive SAP implementation…”
Section: Perceived Environmental Uncertaintymentioning
confidence: 99%